Delville Linford with A.J. Venter, As the Crow Flies: My Bushman Experience with 31 Battalion (Historia, 2021)
As the Crow Flies is the latest in a spate of Border War books to hit the shelves and, no doubt, will be devoured by an ever growing and appreciative audience. The authors of these books put pen to paper for a complex set of reasons. Others do it to "set the record straight" and give meaning to the sacrifices which they and their comrades made on behalf of a government that was the pariah of the world. Yet others, do so to provide a record of their service for posterity.
Keywords: As the Crow Flies; Border War